Molecular Detection and Characterization of the mecA and nuc Genes From Staphylococcus Species (S. aureus, S. pseudintermedius, and S. schleiferi) Isolated From Dogs Suffering Superficial Pyoderma and Their Antimicrobial Resistance Profiles - González-Domínguez, María S.; Carvajal, Hernán D.; Calle-Echeverri, David A.; Chinchilla-Cárdenas, Danny (Frontiers in Veterinary Science, 2020)
Canine Superficial Pyoderma (CSP) is a bacterial infection secondary to several skin diseases of the dog. Staphylococcus pseudintermedius, which is a commensal bacterium of the dog´s skin, is the leading agent found in dogs affected by CSP, which can progress to deep pyoderma. It is also of clinical significance because S. pseudintermedius strains carry antimicrobial resistance genes, mainly the mecA gene. In this descriptive longitudinal study, molecular characterization of bacterial isolates from dogs affected by CSP was performed in addition to phenotyping, antimicrobial profiling, and assessment of resistance carriage status. Fifty dogs (24 females and 26 males) attending the CES University Veterinary Teaching Hospital were included in the study. CSP was confirmed according to clinical signs and cytological examination. Swabs were taken from active skin lesions for bacterial culture, and phenotyping and antimicrobial resistance profiles were assessed using API-Staph phenotyping and the Kirby-Bauer method, respectively. We also performed molecular detection and characterization of the mecA and nuc encoding gene of coagulase-positive Staphylococci. The mecA gene frequency was established by qPCR amplification of a 131bp gene fragment. Data were evaluated by descriptive statistics. Erythema, peeling, pruritus, and alopecia were the predominant symptoms (72%, 56%, and 46%, respectively). We isolated bacteria compatible with Staphylococcus species. from all samples tested. API phenotyping showed 83.1 to 97.8% compatibility with S. pseudintermedius. PCR-genotyping resulted in 15, 3, and 1 isolates positive for S. pseudintermedius, S. aureus, and S. schleiferi, respectively. Isolated strains showed high susceptibility to Imipenem, Ampicillin/Sulbactam, and Rifampicin (100, 94, and 92%, respectively). The highest resistance was against Vancomycin and Trimethoprim/Sulfamethoxazole (98 and 74%, respectively). S. pseudintermedius, S. aureus, and S. schleiferi isolates were cloned and shared 96% sequence homology. Finally, we found 62% carriage status of the mecA gene in isolates of CSP patients, although only 36% of isolates were methicillin-resistant. Identification of three Staphylococcus species causing CSP, high-level resistance against conventional antimicrobials, and carriage of the mecA gene highlight the importance of performing molecular characterisation of bacteria causing dermatological conditions in dogs.